(untitled) (Applied Biological Research, 2023)
High-altitude sojourn may lead to risk factors for high-altitude disorders and subsequent altitude sickness. This study was aimed to analyse the effects of sea level yoga practices on individuals when they ascend to high altitudes (HAs). Healthy male subjects were randomly divided into two groups i) yoga group (n = 43) and ii) control group (n = 44). One month of yoga training was given to the yoga group for 30 min daily. The control group was provided daily routine for one month. Blood samples were collected when subjects were in fasting condition at sea level and at high altitude. Thepulmonary function, blood pressure, cardiovascular and resting metabolic parameters and estimated markers of endothelial homeostasis were monitored at sea level and then at high altitude. The study revealed that yoga group had enhanced pulmonary functions (p < 0.001), maintained blood pressure, and increased endothelial homeostasis markers such as corin and ACE; and showed decrease in VO2resting and hypoxia induced endothelial leak parameters such as Angptl4, sKDR. In control group, the blood pressure, VO2, VCO2, and Angptl4 increased, while ACE, corin, and sKDR decreased. Sea-level yogic intervention before ascending to high altitude was found helpful for individuals.